A framework to support decision making in the selection of sustainable drainage system design alternatives. (1st October 2017) - Wang, Mingming; Sweetapple, Chris; Fu, Guangtao; Farmani, Raziyeh; Butler, David
Abstract: This paper presents a new framework for decision making in sustainable drainage system (SuDS) scheme design. It integrates resilience, hydraulic performance, pollution control, rainwater usage, energy analysis, greenhouse gas (GHG) emissions and costs, and has 12 indicators. The multi-criteria analysis methods of entropy weight and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) were selected to support SuDS scheme selection. The effectiveness of the framework is demonstrated with a SuDS case in China. Indicators used include flood volume, flood duration, a hydraulic performance indicator, cost and resilience. Resilience is an important design consideration, and it supports scheme selection in the case study. The proposed framework will help a decision maker to choose an appropriate design scheme for implementation without subjectivity. Graphical abstract: Highlights: Framework for decision making in SuDS design alternatives selection is presented. It integrates system resilience, pollution control, GHG emissions and costs, etc. The multi-criteria analysis methods of entropy weight and TOPSIS were selected. Framework will help to choose an appropriate design scheme without subjectivity.